Modern Features and Particular Issues of Rotavirus Preventive Vaccination - Marina V. Fedoseenko; Tatiana A. Kaiiuzhnaia; Firuza Ch. Shakhtakhtinskaya; Svetiana V. Tolstova; Arevaiuis M. Selivyan (Педиатрическая фармакология, 2024)
Rotavirus is recognized as one of the worid’s most common pathogens of acute gastroenteritis among children (up to 5 years of age) and has significant impact on chiidhood morbidity and mortality. The recommended by WHO routine vaccination of infants against rotavirus infection has led to notable reduction in incidence, hospitalization and costs associated with rotavirus infection outcomes in countries that have achieved high vaccination coverage. However, we should be aware of several features of rotavirus vaccines implementation as their safety and efficacy depend on it. Despite the absence of rotavirus vaccination within the National Immunization Schedule in Russian Federation and extremely low coverage of rotavirus preventive vaccination, the authors receive many questions from practicing pediatricians regarding cases of rotavirus vaccination. This article includes complete answers for most relevant of them that arise during practical use of rotavirus vaccines.